Do chromatin changes around a nascent double strand DNA break spread spherically into linearly non-adjacent chromatin? - Savic, Velibor (Frontiers in Genetics, 2013)
In the last decade, a lot has been done in elucidating the sequence of events that occur at the nascent double strand DNA break. Nevertheless, the overall structure formed by the DNA damage response factors around the break site, the repair focus, remains poorly understood. Although most of the data presented so far only address events that occur in chromatin in cis around the break, there are strong indications that in mammalian systems it may also occur in trans, analogous to the recent findings showing this if budding yeast. There have been attempts to address the issue but the final proof is still missing due to lack of a proper experimental system. If found to be true, the spatial distribution of DDR factors would have a major impact on the neighbouring chromatin both in cis and in trans, significantly affecting local chromatin function; gene transcription and potentially other functions.